TWO SPECIES OF PROFUSULINELLA (P. ALJUTOVICA AND P. OVATA), EARLY MOSCOVIAN (PENNSYLVANIAN) FUSULINES FROM SOUTHERN TURKEY AND SUBDIVISION OF PRIMITIVE GROUPS OF THE FAMILY FUSULINIDAE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
Early Moscovian (Pennsylvanian) fusulines, Profusulinella aljutovica and Profusulinella ovata, from the Hadim area, southern Turkey are described systematically. They are contained in the bedded limestone (algal fusuline grainstone) of the Yaricak Formation of the Aladag Unit in the Tauride Block. Morphologic analysis of these and similar species suggests: (1) Aljutovella should be synonymous with Profusulinella; (2) Ovatella, Depratina, Staffellaeformes, Aljutovella (Elongatella), Tikhonovichiella, Skelnevatella, and Priscoidella proposed in 1980’s and 1990’s are also synonymous with Profusulinella; and (3) the families Profusulinellidae and Aljutovellidae are not necessary and Profusulinella is included in the subfamily Fusulinellinae placed under the family Fusulinidae.
Keywords: Profusulinella; Early Moscovian; Taurides; Turkey